Gamificação na 8ª Pré-Jornadinha Nacional de Literatura - Andreolla, Renata (2018)
This dissertation, connected to the Postgraduate Program in Literature of the University of Passo Fundo, in the line of research Reading and Formation of Reader has a purpose of analyze the contribution of the gamification in the construction and formation of new readers through the application JornadaApp na Escola that was used as a resource in the 8th PreJornadinha Nacional de Literatura. The theoretical references of this research are based on the studies of Michele Petit (2009, 2013), on the issue of formation of reader; in the studies of James Paul Gee (2003), Jane McGonigal (2012) and Kevin Werbach (2017) in relation to games and gamification; and on about learning and gamification in education, the contributions of Lucia Santaella (2003, 2007, 2013) and Flora Alves (2015).The descriptivequalitative research observed, recorded and analyzed the data through theoretical assumptions, without the interference of the researcher, and concludes the relevance of literary literacy through the gamification practice, realizing that gamification is a viable strategy for the engagement and motivation of the students in the development of competences in the learning of literature, and should be disseminated among the teaching community in order to obtain better results in the matter of forming readers.